Intensity of the creative economy agency and partnership in empowering micro and small enterprises - Awan Setya Dewanta; Sahabudin Sidiq (Economic Journal of Emerging Markets, 2023)
Purpose ─ This paper analyzes the determinants of micro and small enterprise company performance and its employees in Indonesia using a data set covering 2010 – 2019. Method ─ This study uses the robust estimation of the panel data regression method to estimate an alternative least squares regression that does not require strict assumptions and is not sensitive to outliers. Findings ─ The study's findings are as follows: 1) Improving resources, markets, entrepreneurs, and institutions has different impacts on business performance and workers' compensation due to the complexity and size of businesses, 2) The formal education of micro and small business entrepreneurship and institutionalization of partnerships have improved workers' compensation but not business performance, 3) Improving resource access, market orientation, and policies indirectly implemented by the Creative Economy Agency have improved business performance but not workers' compensation. Therefore, programs aimed at enhancing productivity of entrepreneurs and workers through partnerships are a key factor in improving the competitiveness of micro and small enterprises. Originality ─ Four determinants of the business environment of micro and small enterprises were analyzed to determine their impact on entrepreneur and worker performance, in order to identify the key factors contributing to the successful empowerment of these businesses.